Study on Influencing Factors of College Students’ Willingness to Return to Their Hometowns for Entrepreneurship under the Background of Rural Revitalization—— Take the College Students in Shandong Universities in Yantai as an Example - Tan, Tongxin; Yan, Minqi; Zang, Xiaoxuan; Han, Ruijin; Liu, Meijia (Asia Pacific Economic and Management Review, 2025)
As a pivotal national strategy proposed at the 19th National Congress of the Communist Party of China, the Rural Revitalization Strategy carries the mission of comprehensively advancing coordinated development across rural areas in economic, social, cultural, and ecological domains. However, accelerated urbanization has exacerbated the urban-rural divide, leaving rural regions grappling with talent drain and economic stagnation. To address this challenge, the government actively encourages college students to return home for entrepreneurship, aiming to harness their innovative thinking and fresh energy to drive rural economic transformation and achieve the grand vision of rural revitalization. This study examines factors influencing college students’ willingness to return for entrepreneurship in Shandong Province, focusing on universities near Yan City. Key findings reveal that policy support, family dynamics, personal capabilities, entrepreneurial education, and rural environment collectively shape these decisions. The research proposes targeted recommendations to assist governments, universities, and stakeholders in promoting student entrepreneurship and supporting rural revitalization efforts.